Optimal Device and Regimen of Nasal Saline Treatment for Sinonasal Diseases: Systematic Review - Wirach Chitsuthipakorn (2022)
Objective: This review aimed to systematically determine the optimal nasal saline regimen for different types of sinonasal diseases. Data Sources: PubMed, Embase, SCOPUS, Cochrane Library, Web of Science, ClinicalTrials.gov. The last search was on December 6, 2021. Review Methods: Study selection was done by 2 independent authors. Randomized controlled trials and meta-analyses were included. The effects of nasal saline treatment through various devices, saline tonicities, and buffer statuses were evaluated in patients with allergic and nonallergic rhinitis, acute and chronic rhinosinusitis (CRS), CRS with cystic fibrosis, and postoperative care, including septoplasty/turbinoplasty and endoscopic sinus surgery. Results: Sixty-nine studies were included: 10 meta-analyses and 59 randomized controlled trials. For allergic rhinitis, large-volume devices (≥60 mL) were effective for treating adults, while low-volume devices (5-59 mL) were effective for children. Isotonic saline was preferred over hypertonic saline due to fewer adverse events. For acute rhinosinusitis, saline irrigation was beneficial in children, but it was an option for adults. Large-volume devices were more effective, especially in the common cold subgroup. For CRS, large-volume devices were effective for adults, but saline drop was the only regimen that had available data in children. Buffered isotonic saline was more tolerable than nonbuffered or hypertonic saline. The data for CRS with cystic fibrosis and nonallergic rhinitis were limited. For postoperative care, buffered isotonic saline delivered by large-volume devices was effective. Conclusion: Nasal saline treatment is recommended for treating most sinonasal diseases. Optimal delivery methods for each condition should be considered to achieve therapeutic effects of saline treatment.